2018
DOI: 10.1002/2017wr021273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Three‐Phase Relative Permeability and Hysteresis Models on Forecasts of Storage Associated With CO2‐EOR

Abstract: Geological CO2 sequestration in conjunction with enhanced oil recovery (CO2‐EOR) includes complex multiphase flow processes compared to CO2 storage in deep saline aquifers. Two of the most important factors affecting multiphase flow in CO2‐EOR are three‐phase relative permeability and associated hysteresis, both of which are difficult to measure and are usually represented by numerical interpolation models. The purpose of this study is to improve understanding of (1) the relative impacts of different three‐pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…34 A recent study on the impact of hysteresis models on three-phase WAG simulation of a field sector model highlighted the sensitivity of the choice of hysteresis model rather than relative permeability models on simulation results. 35 To mitigate this limitation, it is recommended to calibrate the relative permeability model based on measurements or matching the history data to obtain a reliable prediction. Hence, understanding the active mechanisms involved in the SAG process aimed to be modeled is an important requirement in choosing the appropriate simulator and in modeling the process.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…34 A recent study on the impact of hysteresis models on three-phase WAG simulation of a field sector model highlighted the sensitivity of the choice of hysteresis model rather than relative permeability models on simulation results. 35 To mitigate this limitation, it is recommended to calibrate the relative permeability model based on measurements or matching the history data to obtain a reliable prediction. Hence, understanding the active mechanisms involved in the SAG process aimed to be modeled is an important requirement in choosing the appropriate simulator and in modeling the process.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Hysteresis is defined as the different values of relative permeability and capillary pressure for a given saturation table as a result of saturation history . A recent study on the impact of hysteresis models on three-phase WAG simulation of a field sector model highlighted the sensitivity of the choice of hysteresis model rather than relative permeability models on simulation results . To mitigate this limitation, it is recommended to calibrate the relative permeability model based on measurements or matching the history data to obtain a reliable prediction.…”
Section: Methodsmentioning
confidence: 99%
“…5 This means that carbon capture and storage enhanced oil recovery (CCS-EOR) can be balanced with the dual objective of enhanced oil recovery whilst at the same time storing some of the injected CO 2 permanently in the depleted reservoir. [6][7][8][9][10][11] Finally, in a recent review study it was suggested that it is feasible to use CO 2 -EOR to enhance shale gas recovery instead of using conventional water-based fracturing fluids. It was then concluded that the process can be applied with the objectives of drilling, fracturing and sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…Existing uncertainty studies for GCS primarily focus on uncertainties stemming from porosity, permeability, and operational factors (e.g., injection scheme) [6,[14][15][16][17][18][19][20]. Only a few studies have examined the impact of uncertain reactive surface areas on GCS performances.…”
Section: Introductionmentioning
confidence: 99%